DETERMINATION OF THE COMPLEX POTENTIAL FLOW AROUND TWO PARALLEL AIRFOILS - Armengol, Jan Mateu; Salinas Sedano, Carlos (Revista Ciências Exatas, 2014)
This paper aims to present a methodology to calculate the complex potential flow around two parallel airfoils. For this purpose, the complex potential flow around two circular cylinders is determined based on the Circle Theorem. Thereafter, a double application of the Joukowsky Conformal Transformation transforms the two circular cylinders into the two airfoils. Moreover, the circulation around the airfoils is determined according to the Kutta Condition. To validate the formulation, the stream function over different configurations is presented and then the streamlines identifying the body surfaces are verified.